(3GdJbUi aj eYQaI TjhN eGdc Hf CfS QVi Gddg Yfg aj GdehWC hPcQ CMGOjKgs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s ((3CMeO Hf fYeI Gddg GdCTehfi s)
(3ChdgG (B:s
(3bGd CHh YeQ GdfeQi GdMeO ddg TcQkG Ydi eGgOi aChdi GdCehQ Hef fUM faSg hGdge QTOg eYQaI GdSff GdJi gi GdHjGf deLed GdbQBf s
(3BNQgG (B:s
(3hgPG GdMOjK YfO eYf hSdjeGf GHf HQO heUYH GdRHjQi ai GdehWC Ohf ZjQge HgPG GdESfGO JeJ GdRjGOGJ GdJi de jbY ai GdehWC Je LejY GdOjhGf s
(3GdfSNI efbhdI hebGHdI Ydi fSNI HNW GdeMOK TgGH GdOjf CMeO Hf Ydi GdbQWHis
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs